Uso de lodo gerado em estação de tratamento de água na fabricação de bloco cerâmico ecológico para uso em construções rurais - Alvarenga, José Mauro Corrêa (2019)
Sludge generated at the Water Treatment Plant (ETA), which is the residue mainly formed in the decanter or the filter, is a material composed of solid, organic and inorganic substances, which is most often disposed of incorrectly in water bodies further polluting the environment. There are some options for the use of sludge from ETA, such as disposal in landfills and the incorporation in ceramic blocks that can be used in agricultural constructions. This last one is in expansion, many agricultural constructions like stables, small places of storage of inputs can be constructed with the call ecological ceramic blocks, in which the incorporation of different types of residues, in this case mud. In view of this scenario the objective of this work is to propose a feasibility study on the use of sludge being added in a ceramic block, thus verifying its viability in agricultural construction. The analyzes were done in the laboratory of a ceramics industry, initially it was carried out test in test bodies, where it was evaluated the plasticity, granulometry and Bigot's Curve, besides the primary analyzes of Moisture, Loss to Fire, Total Loss, Retraction of Drying, Burn Retention, Total Retention and Water Absorption of treatments with 100%, 70%, 50% and 20% of sludge, in addition to the standard mass. With the results in test specimens, a ceramic block with 20% and 5% of sludge was made, where a visual inspection, geometric characteristics, water absorption index and resistance to compression were made, all methodologies following NBR 15270: 2017. The tests in the test specimen showed that 100% of sludge could not be used, and the result that is closest to the standard established by ABNT for ceramic ceramic blocks was the treatment with 20% sludge, where even moisture close to double the standard mass the retraction and burning were very close to the standard mass. The ceramic blocks made with mud had results very close to the standard block, especially when it comes to water absorption and compressive strength, these being the most important factors when it comes to ceramic blocks of the type seal. With this study it can be concluded that it is possible to use sludge in the manufacture of ceramic blocks in the proportion of 20% and 5%.